Obtaining informed consent in non-Western contexts: reflections on fieldwork experience Zimbabwe - Jeko, Ishwael; Mangwaya, Ezron; Blignaut, Sylvan (UV/UES, 2016)
Current ethics frameworks for regulating social science research scent to be based mainly on Western sociocultural traditions, arguably making it difficult for researchers in non-Western contexts to use them as ethics guides. Yet, these frameworks tend often to be used, un-adapted, as default ethics compasses to guide the conduct of research in non-Western contexts. In tins article, the authors reflect on their experiences in obtaining informed consent for an educational research study in Zimbabwe using a Western-based ethics protocol. The experiences are reflectively interpreted in the context of literature with a view to suggesting some sensitive issues that need to be taken into account when seeking informed consent of research participants its non-Western contexts, particularly in Africa.